Coordinated Development of Urban Transportation Structure Optimization and Energy Conservation, and Emission Reduction Under the Low-Carbon Background in Lanzhou, China - Zheming Shi; Yongsheng Qian; Junwei Zeng; Xu Wei; Minan Yang (Systems)
Under the context of low-carbon travel, promoting the green and environmentally friendly upgrade of urban transportation and optimizing urban transportation structures are of great significance in reducing carbon emissions. Exploring the pathways and methods to achieve green and low-carbon goals in urban transportation is a key research objective. Accordingly, this study constructs a multi-objective optimization model to optimize the transportation structure of Lanzhou City and quantitatively verifies the optimization effects through carbon emission calculations and coordination evaluations. The results indicate that (1) optimizing urban transportation structures can reduce energy consumption and emission levels but cannot achieve the “carbon peaking” goal; (2) developing urban rail transit has a significant positive impact on energy saving and emission reduction; (3) the development of green transportation is closely integrated with and mutually influenced by slow-moving transportation, showing both synergy and constraints; and (4) under the comprehensive restriction scenario, despite higher energy consumption and emission values, better coordination is achieved, making it the most suitable optimization plan aligned with the green transportation development concept.